1985
DOI: 10.1111/j.1476-5381.1985.tb08910.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tyramine on noradrenaline outflow and electrical responses induced by field stimulation in the perfused rabbit ear artery

Abstract: In the perfused rabbit ear artery the basal outflows of noradrenaline (NA) and 3,4‐dihydroxyphenylglycol (DOPEG) were < 1 ng g−1 and 1–2 ng g−1 wet weight of tissue respectively. Field stimulation increased outflows of NA and DOPEG in a frequency‐dependent manner, and they reached the maximum value at frequencies over 5 Hz. Tyramine (1 × 10−6 − 1 × 10−4 M) increased basal outflow of NA and DOPEG, in a dose‐dependent manner. This effect was not blocked by tetrodotoxin (TTX, 3 × 10−7 M), but was prevented by pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…The first phase may contain mostly a P2X receptor-mediated purinergic component and the second phase, mainly an α 1 -adrenoceptormediated adrenergic component (20). Tyramine is capable of facilitating outflow of noradrenaline during nerve excitation, in addition to an increase in the basal outflow of noradrenaline (3). In the present study, we were able to confirm that tyramine facilitated the second phase of double peaked vasoconstrictions, but having little effect on the first one.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The first phase may contain mostly a P2X receptor-mediated purinergic component and the second phase, mainly an α 1 -adrenoceptormediated adrenergic component (20). Tyramine is capable of facilitating outflow of noradrenaline during nerve excitation, in addition to an increase in the basal outflow of noradrenaline (3). In the present study, we were able to confirm that tyramine facilitated the second phase of double peaked vasoconstrictions, but having little effect on the first one.…”
Section: Discussionsupporting
confidence: 76%
“…The subtype of α-adrenoceptors involved in the tyramine-induced response was generally recognized to be an α 1 -adrenoceptor subtype in many blood vessels (3,5). Several lines of evidence have suggested that there is heterogeneity of α 1 -adrenoceptor subtypes located in the neuroeffector junction and extrajunctional region (6 -9).…”
Section: Introductionmentioning
confidence: 99%
“…The ej.p. is resistant to aadrenoceptor antagonists, but can be blocked by guanethidine or chemical denervation of adrenergic nerves by 6-hydroxydopamine (Miyahara & Suzuki, 1985), thereby indicating that this potential may be generated by substances released from perivascular adrenergic nerves. By comparing the ej.p.…”
Section: Ach-induced Hyperpolarization Ofsmooth Muscle Membranementioning
confidence: 99%
“…2 " 7 It has been shown in in vivo studies that pressor responses to exogenous and neurogenically released norepinephrine may be mediated by different a-adrenoceptor subtypes. 38 " 10 In the canine hind limb and the pithed rat, responses to sympathetic nerve stimulation are selectively blocked by a,-adrenoceptor antagonists, but responses to exogenous norepinephrine are attenuated by a 2 -adrenoceptor antagonists.…”
mentioning
confidence: 99%
“…Tyramine is an indirect acting amine that displaces norepinephrine from adrenergic terminals by a calcium-independent process. 3435 Although tyramine may possess some direct activity, 38 vasoconstrictor responses to this agent are mainly indirect in the feline mesenteric vascular bed because they are almost entirely blocked by cocaine, an agent that blocks neuronal uptake of norepinephrine. 34 -39 Although yohimbine reduced responses to tyramine by approximately 50%, the effects of this agent on responses to electrical stimulation of the sympathetic by guest on May 11, 2018 http://circres.ahajournals.org/ Downloaded from nerves are difficult to interpret since presynaptic and postsynaptic blocking actions of the antagonist would be expected to have opposing effects on the pressor response.…”
mentioning
confidence: 99%